A família no discurso da campanha publicitária televisiva da margarina “Qualy”: outro modelo, a mesma história - Oldoni, Sueza (2014)
This work aims to analyze how the margarine commercials "Qualy", through television, create a particular imagery around the very concept of family. For this purpose, we raise the following question: how are the effects of meaning, concerning this concept, created in the “Qualy” margarine television advertising? To answer this question we focus on the goal of understanding Sadia discourse using a “Qualy” advertise campaign, produced in 2009, which consist of eight commercials. Our theoretical purpose is to seek the light of French Discourse Analysis of Michel Pecheux and Eni Orlandi, trying to understand the workings of these effects of sense on family which come from this advertising intent. The campaign propagation took place through open national television media between 2009 and 2010. In the course of its eight episodes it tells a little story about a particular family dynamic, and by the end of each there is an idea of continuity that invites the audience to look forward for the next chapter, which creates the chapter feature of the campaign, like the simulation of a small soap opera. The family, protagonist of this story, is composed of three members: a mother (Anne), son (Rafa) and grandmother (Theresa), plus a fourth character who does not live with his family but is often around, it is the mother's boyfriend (Beto). With the analysis process it was possible to notice that although the surface of discourse reveal an organization of contemporary family, the relationships established in this family, even if sometimes conflicting, substantially reveal that the traditional family, which has always been present in commercials, above all, the margarine ones. So, we work with meanings that may propose new ideas and concepts are already existing meanings.